Age influence on cut-out resistance of sutured meniscus: An experimental cadaveric study - Peña Trabalón, Alejandro; Estébanez-Campos, María Belén; Moreno-Vegas, Salvador; Pérez-Blanca, Ana; Prado-Novoa, María (My University, 2023)
Surgical treatment of meniscal root detachment is changing from partial meniscectomy to root reinsertion with sutures due to alterations in the knee joint contact biomechanics and early cartilage loss development. Suture fixation techniques of meniscal roots can be grouped into transtibial and in situ fixations, both techniques pierce the meniscal horn to pass a suture thread through the hole and reconnect meniscus to bone. Despite its importance for the survival of the repair, few works focus on determining the resistance of meniscal tissue cut-out by direct thread traction on the suture hole and, as far as we are aware, the influence of age on this resistance has not been yet studied.
Keywords: Menisco - Cirugía; Sutured meniscus; Meniscal root detachment; Surgical treatment; Age influence